1997
DOI: 10.1136/bmj.315.7115.1039
|View full text |Cite|
|
Sign up to set email alerts
|

Randomised controlled trial to evaluate early discharge scheme for patients with stroke

Abstract: Early discharge with specialist community rehabilitation after stroke is feasible, as clinically effective as conventional care, and acceptable to patients. Considerable reductions in use of hospital beds are achievable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 18 publications
4
154
0
1
Order By: Relevance
“…Rudd et al reported the most widely dispersed admission scores for both the BI and MMSE; in this study, 1 standard deviation in scores ranged from 11 to 19 in the BI and 14 to 28 on the MMSE. 15 This wide variation in scores reflects more inclusive admission in this particular study that was not seen in the others. Across all eight trials, the majority of outcomes were either similar between ESD and the control group or in favour of ESD.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 65%
See 4 more Smart Citations
“…Rudd et al reported the most widely dispersed admission scores for both the BI and MMSE; in this study, 1 standard deviation in scores ranged from 11 to 19 in the BI and 14 to 28 on the MMSE. 15 This wide variation in scores reflects more inclusive admission in this particular study that was not seen in the others. Across all eight trials, the majority of outcomes were either similar between ESD and the control group or in favour of ESD.…”
Section: The Canadian Journal Of Neurological Sciencesmentioning
confidence: 65%
“…Holmqvist et al explicitly used an MMSE score of 23 in their inclusion criteria 10 and two others reported average admission scores of 28 and 21, respectively. 6,15 In these three studies, the mean score on admission was 24/30. Similar to BI, the study with the widest dispersion of admission MMSE scores was Rudd et al, 15 in which 1 standard deviation from the mean ranged from 14 to 28.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations